PERMOHONAN DISPENSASI NIKAH DI PENGADILAN AGAMA MAROS KELAS 1B PERSPEKTIF HUKUM ISLAM - Nur Umniati Kalsum; Lomba Sultan; Muhammad Fajri (Universitas Islam Negeri Alauddin Makassar, 2023)
The main problem of this research is the application for marriage dispensation at the Maros Religious Court Class 1B Islamic law perspective (case study 2019-2021). as well as the factors that influence the rise of marriage dispensation applications in the Maros religious court, the type of research used is qualitative using a syar'i approach and a normative juridical approach. The results of this study, namely, the judge's consideration in granting a marriage dispensation application refers to the Supreme Court Regulation Number 5 of 2019 concerning Guidelines for Adjudicating a Marriage Dispensation Application, other than that the judge's consideration in granting a marriage dispensation application, the judge considers the negative impact or harm more as there are element of emergency in the application for dispensation of marriage. In Islamic law it allows early marriage on the condition that it is mature, that maturity does not depend on age, but depends on intelligence or maturity of mind to carry out the marriage. As for the factors that influence the rise of marriage dispensation applications at the Maros Religious Court, namely economic factors, dropout factors, promiscuity factors and the high salary for marriage. The implication of this research is that there is a need for community participation in minimizing the number of marriage dispensation cases at the Maros Religious Court, especially parents so that they often remind children about religious teachings and supervise them in all things, both the child's social environment and the use of social media so that the child does not fall into the trap. in promiscuity which resulted in the child getting pregnant before marriage.